FDI inflows and R&D activity in developing countries - Wan Ngah, Wan Azman Saini; Mahamad Zakaria, Muhammad Farhan; Tee, Chee Lip; Tun, Yin Li (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study investigates the impact of FDI inflows on R&D activity in 48 developing countries for the 1996-2013 periods. The results based on the system Generalized Method of Moment (GMM) estimator show that FDI inflows discourage R&D activity in developing countries. This finding is consistent with the view that foreign R&D investment is a substitute for domestic R&D efforts. This suggests that firms in developing countries are more inclined toward imitation of the existing products rather than innovation of a new technology. However, domestic R&D activity appears to benefit from imports of machinery and equipment, stronger legal protections, better human capital and higher economic growth.